2019
DOI: 10.1364/jocn.11.000397
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Optimal Deployment of a C-RAN With Hybrid Fiber/FSO Fronthaul

Abstract: Centralized radio access network (C-RAN) has been considered as an architectural solution able to reduce capital and operational expenditure in dense 5G cellular networks, while allowing better network performance. The C-RAN approach decouples baseband units from antenna sites and places them in selected locations, connected by the so called fronthaul links. These links require expensive high capacity connections, thus calling for cost-efficient deployment. This paper presents a hybrid fronthaul solution for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Furthermore, the extra flexibility brought by free-space optics (FSO) in the MFH segment can be beneficial to lower the deployment cost. In [19], it is shown that FSO-based links are costeffective in dense-urban areas as they make it possible to save around 50% of the total network deployment cost. Network function virtualization (NFV) reduces the hardware complexity and, therefore, might be an effective solution for further cost reduction.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the extra flexibility brought by free-space optics (FSO) in the MFH segment can be beneficial to lower the deployment cost. In [19], it is shown that FSO-based links are costeffective in dense-urban areas as they make it possible to save around 50% of the total network deployment cost. Network function virtualization (NFV) reduces the hardware complexity and, therefore, might be an effective solution for further cost reduction.…”
Section: Related Workmentioning
confidence: 99%
“…Pros and cons of RoF-based MFH solutions have been mainly assessed in terms of the PHY-layer performance (e.g., capacity [2], [8]- [13], latency [3], [14], [15], reliability [5], [16], [17]), optimization of the deployment costs [18], [19], placement of the baseband processing functionalities [20], [21], and energy efficiency [22]- [27]. Yet, a fair analysis in terms of total cost of ownership (TCO) of their deployment is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…I T is expected that the number of devices that will use the fifth generation (5G) of wireless communication technology will reach tens or even hundreds of billions world wide, and the total data volume demand is predicted to increase to over 175 Zettabytes until 2025 [1]. To support this tremendous demand for wireless data, there are two promising key strategies, namely ultra dense deployment and centralized processing [2]- [6]. Here, ultra dense deployment refers to the use of low power, dense small cell networks, where the distance between the base stations (BSs) and the mobile devices (MDs) is reduced significantly compared to the current networks which leads to higher achievable data rates.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we are considering the uplink 1 and to overcome the problem of multiple access interference, centralized processing can be used, where all received signals in the network are processed at a central unit (CU), and thus, interference can be efficiently mitigated. Cloud radio access networks (C-RANs) are combining these two features, where several remote radio units are typically directly connected to the CU [4]- [6]. However, to cover a certain area and to reach high data rates, C-RAN architectures mostly rely on expensive optical fiber links to connect each remote radio unit to the CU [6], [10].…”
Section: Introductionmentioning
confidence: 99%
“…More and more DAS suppliers are providing digital DAS (DDAS) solutions to solve these problems [4]. DDAS systems are developing towards software defined radio (SDR) and centralised radio access network (C-RAN) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%